Stability Analysis of the Development Mathematical Models for the Spread of Covid-19 Effects of Vaccination and Campaigns as Processes in Controlling the Spread of Disease - Curex, Nola; Toaha, Syamsuddin; Kasbawati (Proximal: Jurnal Penelitian Matematika dan Pendidikan Matematika, 2022)
Novel Coronavirus or corona virus is a type of virus that was first discovered in 2003, until now this virus has mutated to form a new type of corona virus (SARS-CoV-2) and causes the emergence of a disease called Coronavirus Disease-19 (COVID-19). The purpose of this study was to see how the influence of vaccination and campaigns in the disease control process with showed sensitivity analysis to determine the parameters that affect the basic reproduction number , and stability analysis. The results obtained from the sensitivity analysis, which found a parameter relationship with which could increase and decrease the value of , and the stability analysis showed the effect of changes in the stability of the equilibrium point due to changes in the values ​​of the parameters , and . The model simulation shows that vaccination and campaigning can control the spread of COVID-19 disease.